Normal, Abnormal Book-Tax Differences And Accounting Conservatism - Koubaa, Rakia Riguen; Jarboui, Anis (Asian Academy of Management (AAM), 2017)
The present paper investigates the effect of book-tax differences on the accounting conservatism (as a proxy for financial reporting quality). The major objective of this study was to examine the extent to which regulatory and opportunistic information in book- tax differences influence accounting conservatism. We also aim to examine if book-tax differences are a signal of “bad news” for investors. Using publicly available financial statements from 2005 to 2012 for 28 Tunisian listed firms on the Tunis Stock Exchange and operating in the industrial and commercial sectors, we use a current measure for accounting conservatism and documents that observation with large book-tax differences are associated with low levels of accounting conservatism. Also, we find that firms with abnormal book-tax differences and normal book-tax differences exhibit less accounting conservatism. Overall, the results suggest that the total and differing components of book- tax differences have differential implications on accounting conservatism. Our research is valuable for researchers, shareholders as well as regulators. For researchers, it appears to an innovative area for future research. For shareholders, it shows the role of the information transmitted by book-tax differences into the analysis of earnings quality published by firms. This study also helps regulators to improve accounting rules and tax rule.